Design and Evaluation of a Web-Based Batik Marketing System Using Prototype Model - Dedi Santosa; Sumardiono Sumardiono; Mukhfid Mukhfid; Surianti Surianti; Miko Priambada (Jurnal Simantec, 2026)
The development of information technology has driven digital transformation in various in-dustrial sectors, including the batik home industry. However, the Batik Binar MSME still fac-es marketing challenges related to the public's understanding of the philosophy of batik and the use of traditional sales systems. This study aims to design a dynamic and easy-to-use web-based batik sales information system, as well as provide education to the public about batik. The research method used is descriptive-qualitative, with data collection through observation, interviews, and literature studies. The system development used a prototype method that in-cludes the stages of communication, planning, modeling, construction, and evaluation. The results showed that the system was successfully designed with features such as product man-agement, transactions, and reports. Black box testing and user questionnaires showed a system feasibility level of 77.9%, which means it is feasible to implement. This system can support batik marketing more efficiently and effectively.